From Socialism to Capitalism: Structural Poverty of Indigenous Women in West Kalimantan, Indonesia - Rupita Rupita; Nikodemus Niko (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
The issue of indigenous women is closely related to the issue of poverty. Women who inhabit rural areas in Indonesia cannot separate from the conditions of life that are poor and completely limited. This paper tries to reflect Karl Marx's thoughts about poverty and injustice that occur in a country because of a structured system. This paper uses a qualitative approach by presenting primary and secondary data. Primary data collection through interviews and field observations, while secondary data through reading readings of scientific studies results in journal articles, policy papers, and government agencies' data. The results of this paper presents: 1) The concept of Marx that poverty is the expression of structural poverty; 2) Poverty among indigenous Dayak Benawan women in rural West Kalimantan, Indonesia, is not only cultural but also structural poverty that expressed limited access to education, health, and a decent standard of quality life; 3) From the era of classical philosophy to modern technology era today, the poverty that has occurred centuries ago today, indigenous women of Dayak Benawan in rural areas are still faced with.